Digitizing learning modules without internet quota to accelerate education equity in Pabean Udik Village Indramayu - Achmad Zuchriadi; Fajar Rahayu; Silvia Anggraeni; Muhammad Alif Razi; Jati Kinsela Brajamusti; Mutiara Putri R Darmawan (Jurnal Mandiri IT, 2023)
Education equality for the Indonesian people still needs to be improved; for example, in Indramayu, the average length of schooling for the community has only reached 6.52 years (2021) and 6.83 years (2022), still below the 12-year compulsory education program. One way of equitable distribution of education through digitisation of the Education module still needs to be solved, especially related to uneven internet access facilities and the high price of internet quota. Therefore, it is necessary to carry out this activity so that a system that contains digital learning modules can be produced without using internet quota. This activity aims to digitise learning modules that can be accessed without internet quota to accelerate education equity for Pabean Udik Village Indramayu school students. Activities are carried out by designing a system consisting of hardware, web-based applications and learning module content, both K-13 modules and Virtual laboratories. The result obtained is the availability of a system that contains learning module content and virtual laboratories that can be accessed without internet quota using smartphones, tablets and computers. This system is expected to be a solution for equitable development, especially for students in Indramayu, to increase students' knowledge even though the average school time is still below national standards. This system can also be implemented in other regions to accelerate education equity in Indonesia.